Development and applicability of a dignity‐centred palliative care programme for people with idiopathic pulmonary fibrosis: A qualitative‐driven mixed methods study - Yasuko Igai; Sarah E. Porter (Nursing Open, 2023)
Abstract Aims This study evaluated the acceptability of a dignity‐centred palliative care programme for people with idiopathic pulmonary fibrosis by converging perceptions of living with idiopathic pulmonary fibrosis qualitative data and quantitative data. Design The qualitative‐driven mixed methods research addressed the study aim by using a convergent design. This single arm, non‐randomized study used purposive sampling. Methods Interviews with 12 stable outpatients with IPF provided qualitative data. Their quantitative data were from six scales: self‐esteem, health‐related quality of life, anxiety, depression, dyspnoea, cough and programme satisfaction. Intervention was three educational modules: symptom management, enhancing daily activities and life reviews. Results Semi‐structured interviews yielded eight categories. Self‐esteem was not statistically significantly changed. Dyspnoea symptoms improved significantly. Participants (n = 9) holding positive attitudes for living with idiopathic pulmonary fibrosis, had improved lifestyle behaviour and improved or maintained self‐esteem. The meta‐inference regarding idiopathic pulmonary fibrosis perceptions were related to changes in self‐esteem.